Pemanfaatan Eceng Gondok Fermentasi terhadap Karkas dan Non Karkas Domba Lokal Jantan Lepas Sapih - Lusiyana Wanti Sihite (Jurnal Peternakan Integratif, 2014)
Water hyacinth is one of the communities that waste can be used to meet the needs of the lack of green feed ram. Water hyacinth can be used as animal feed with fermented by local microorganisms (MOL) and Tricoderma harzianum to raise the level of palatability and nutrient content of the water hyacinth . The experiment was conducted at the Laboratory of Animal Biology, Animal Husbandry Study Program, Faculty of Agriculture, University of Sumatera Utara in August to November 2013 using 20 local ram with an average body initial weight 8.30 ± 1.16 kg/head. The design used in the study was a completely randomized design (CRD) using 5 treatments and 4 replications. Treatment consists of P0: 0% (without fermented water hyacinth), P1: 60% fermented water hyacinth by MOL, P2: 60% fermented water hyacinth by Trichoderma harzianum, P3: 100% fermented water hyacinth by MOL, P4: 100% fermented water hyacinth by Trichoderma harzianum. The results showed that administration of fermented water hyacinth by MOL and Trichoderma harzianum had no significant effect (P>0.05) on carcass weight, carcass percentage, non carcass weight and non carcass percentage.  The average for carcass weight (kg/head) for treatment P0,P1, P2, P3 dan P4 were 3.06, 2.93, 3.12, 3.12 and 2.76, respectively. Average carcass percentages (%) were 38.47, 36.66, 36.82, 36.09 and 34.38, respectively. Average non carcass weight (kg/head) were 4.65, 4.31, 4.60, 4.38 and 3.82, respectively. Average non carcass percentages (%) were 58,73, 53.91, 55.02, 50.82 and 52.89, respectively. The conclusion of this study is the utilization of water hyacinth fermentation had no significant on carcass weight, carcass percentage, non carcass weight and non carcass percentage. Keywords: Fermented Water Hyacinth, Local Microorganisms, Trichoderma harzianum, Carcass, Non Carcass, Local Ram.